2002
DOI: 10.1128/jcm.40.3.1071-1072.2002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Performance of Herpes Simplex Virus Type 1-Specific Serologic Assays from MRL and Meridian Diagnostics

Abstract: Two companies, MRL and Meridian Diagnostics, have developed Food and Drug Administration-approved herpes simplex virus type 1 type-specific enzyme immunoassays. The sensitivity, specificity, and overall testing efficiency of these assays were 98.2, 93.8, and 96.6% for MRL and 98.8, 99.0, and 98.1% for Meridian, making both of these kits suitable for use in the clinical lab.The herpes simplex viruses (herpes simplex virus type 1 [HSV-1] and HSV-2) are important causes of disease worldwide. HSV-1 is the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The selection of this cutoff was based on clinical trials indicating that the use of this cutoff results in a high correlation with gold standard assays such as Western blot and the ability to isolate infectious virus in cell culture. 55,56 Using this cutoff, we found that there is a statistically significant association between HSV-1 reactivity and the RBANS total score as well as the immediate memory index of the RBANS. The use of other cutoffs did not alter the statistical relationship between HSV-1 reactivity and the RBANS total score or the immediate memory score (Table 3).…”
Section: Commentmentioning
confidence: 97%
“…The selection of this cutoff was based on clinical trials indicating that the use of this cutoff results in a high correlation with gold standard assays such as Western blot and the ability to isolate infectious virus in cell culture. 55,56 Using this cutoff, we found that there is a statistically significant association between HSV-1 reactivity and the RBANS total score as well as the immediate memory index of the RBANS. The use of other cutoffs did not alter the statistical relationship between HSV-1 reactivity and the RBANS total score or the immediate memory score (Table 3).…”
Section: Commentmentioning
confidence: 97%
“…In cross-sectional studies, HSV-1 and HSV-2 gG enzyme immunoassays have demonstrated both high sensitivity and specificity (4,8,14,16,17). However, prior evaluations of type-specific assays have reportedly detected frequent changes in an individual's gG antibody status from positive to negative over time.…”
mentioning
confidence: 99%
“…These assays use baculovirus recombinant gG constructs, are Food and Drug Administration approved for testing sexually active adults and pregnant women, and are commercially available. In comparison to Western blot assays, the sensitivity and specificity of the Focus HSV-2 ELISA are 98 and 95%, respec-tively, while those of the Focus HSV-1 ELISA are 98 and 94%, respectively (16,17). Laboratory Tests.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of studies have concluded that only glycoprotein G (gG2) expresses epitopes specific for HSV-2 (14, 21). Consequently, this glycoprotein has been used as the basis of type-specific serological assays for the diagnosis of HSV-2 infection (1,2,7,19,20). However, epitope mapping of gG2 by Levi et al (11) suggested that some epitopes may cross-react with HSV-1-specific antibody.…”
mentioning
confidence: 99%